PENGARUH EXPERIENTIAL MARKETING TERHADAP REVISIT INTENTION MELALUI KEPUASAN SEBAGAI VARIABEL INTERVENING ( Studi Pada Pengunjung Trans Studio Mini Transmart Rungkut Surabaya ) - ARI WIJAKSONO, RENDY (Jurnal Ilmu Manajemen (JIM), 2018)
Trans studio mini being a differentiation strategy for visitors who want to feel the excitement like playing on a vehicle owned by Trans Studio Bandung. The application of experiential marketing in trans studio mini can be felt when playing bumper car rides, new york swing, crazy cab coasters, timezone, until the atmosphere created can provide unique experiences and impress visitors because it touches their visual and emotional and is expected to provide satisfaction according to the expectations of visitors trans studio mini and is expected to increase visitors intention to revisit in the future. The purpose of this study was to analyze and discuss the effect of experiential marketing on the revisit intention through satisfaction as an intervening variable for visitors of the trans studio mini transmart Rungkut Surabaya. Data of this study was collected from 220 respondent as sample. The respondents in this study were visitors who were at least 19 years old and had visited Trans Studio Mini 2 times in the past 6 months. The data were annalyzed using Path Analysis by AMOS software 21. The result showed experiential marketing has significant on satisfaction, satisafaction has significant on revisit intentition and experiential marketing has significant on revisit intention. Keywords: experiential marketing; kepuasan; revisit intention.